Manajemen Manajemen Pelaksanaan Program Pembelajaran Bahasa Arab Di Pondok Pesantren Sunan Kalijogo Surabaya - Agus Wahid Hasan; Danial Hilmi (Tarbiyatuna: Jurnal Pendidikan Ilmiah, 2022)
This study discusses the implementation of the Arabic language learning program held at the Sunan Kalijogo Islamic Boarding School, with a focus on implementation management and the problems faced. This research uses descriptive qualitative method. Collecting data through observation, interview, and documentation techniques. While the data analysis through interactive qualitative analysis technique which consists of data reduction, data presentation and drawing conclusions. The results showed that the management of the implementation of the Arabic language learning program at the Sunan Kalijogo Islamic boarding school went well, seen from the activities the participants were very enthusiastic about participating in the course program, namely the participants could take part in the activities until the specified time limit. In order to maximize language learning, Arabic is used as a daily communication tool. The problems faced by Islamic boarding schools are the limitations of teaching staff, facilities and infrastructure and management in the learning program. Even though there are shortcomings, the learning program held by the cottage can still run smoothly and well, where in the allotted time (3 months), the participants have been able to master the Arabic language well.